Labour Supply in a Two-Period Model: The Effect of a Nonlinear Progressive Income Tax - Blomquist, N. Soren (Review of Economic Studies, 1985)
Earlier studies of labour supply in a life cycle context have typically either neglected taxes completely, or represented the income tax by a linear function. The present paper studies how the qualitative conclusions of a “traditional” life cycle model of labour supply are changed when a nonlinear tax is introduced into the model. It is shown that the comparative statics results, and the characterization of the consumption and labour supply paths, depend critically on whether capital and labour income are taxed jointly or separately, and on the progressivity (nonlinearity) of the income tax. Few of the results valid for a linear income tax carry over to the nonlinear case.